Proton Sensing on the Ocular Surface: Implications in Eye Pain - Comes, Núria; Gasull, Xavier; Callejo, Gerard (Frontiers in Pharmacology, 2021)
Protons reaching the eyeball from exogenous acidic substances or released from damaged cells during inflammation, immune cells, after tissue injury or during chronic ophthalmic conditions, activate or modulate ion channels present in sensory nerve fibers that innervate the ocular anterior surface. Their identification as well as their role during disease is critical for the understanding of sensory ocular pathophysiology. They are likely to mediate some of the discomfort sensations accompanying several ophthalmic formulations and may represent novel targets for the development of new therapeutics for ocular pathologies. Among the ion channels expressed in trigeminal nociceptors innervating the anterior surface of the eye (cornea and conjunctiva) and annex ocular structures (eyelids), members of the TRP and ASIC families play a critical role in ocular acidic pain. Low pH (pH 6) activates TRPV1, a polymodal ion channel also activated by heat, capsaicin and hyperosmolar conditions. ASIC1, ASIC3 and heteromeric ASIC1/ASIC3 channels present in ocular nerve terminals are activated at pH 7.2 to 6.5, inducing pain by moderate acidifications of the ocular surface. These channels, together with TRPA1, are involved in acute ocular pain, as well as in painful sensations during allergic keratoconjunctivitis or other ophthalmic conditions, as blocking or reducing channel expression ameliorates ocular pain. TRPV1, TRPA1 and other ion channels are also present in corneal and conjunctival cells, promoting inflammation of the ocular surface after injury. In addition to the above-mentioned ion channels, members of the K2P and P2X ion channel families are also expressed in trigeminal neurons, however, their role in ocular pain remains unclear to date. In this report, these and other ion channels and receptors involved in acid sensing during ocular pathologies and pain are reviewed.